THU0412 Treatment with neridronate in children and adults with osteogenesis imperfecta: data from open-label, not controlled, three-year italian study. (15th June 2017) - Fassio, A; Idolazzi, L; Viapiana, O; Benini, C; Vantaggiato, E; Giollo, A; Rossini, M; Gatti, D
Abstract : Background: Osteogenesis Imperfecta (OI) is a rare generalized connective tissue disease. Its main features are skeletal fragility and substantial growth deficiency [1]. Currently, bisphosphonates showed to increase bone mineral density (BMD). A positive effect on prevention of fractures both in adults and in children is reported by some studies, but generally data are still inconsistent [2]. Neridronate is an amino-bisphosphonate licensed in Italy for the treatment of OI. Objectives: to assess the long-term efficacy and safety of the treatment in patients with OI. Methods: the patients were divided by age into two groups and observed for 3 years: 55 patients younger than 20 years old and 114 patients older than 20 years old. Neridronate was administered by i.v. infusion at the dosage of 2 mg/kg, up to a maximum of 100 mg at three months intervals. DXA of the lumbar spine, hip and ultradistal radius were evaluated every 6 months. Blood calcium, phosphate, bone turnover markers and fasting urinary calcium/creatinine ratio, were obtained at baseline and every 3 months. Results: the mean lumbar spine and total hip BMD and BMC significantly increased from baseline up to month 36 in both patients groups. The mean ultradistal radius BMD significantly increased from baseline to any time point in patients younger than 20 years, while, in patients older than 20 years, BMD significantly increased from baseline only at month 18, 30 and 36 respectively. The mean ultradistal radius BMC significantly increased from baseline to any time point in patients younger than 20 years, while there were no substantial or statistically significant changes from baseline to any time point in patients aged older than 20 years. The mean number of fractures observed in the 3 years of treatment was significantly lower than that observed in the 3 years before the start of treatment in both groups (table 1 ). Most of AEs were symptoms of an acute phase reaction, which was reported in 47.3% of patients younger than 20 years and in 22.8% of those older than 20 years. Serious adverse events (SAEs) were reported in 19 patients (34.5%) younger than 20 years and in 26 patients (22.8%) aged older than 20 years. None of the reported SAEs in both groups was considered as treatment-related. Conclusions: long-term treatment with i.v.neridronate has positive effects on BMD, BMC, bone turnover markers and fracture risk with a good safety profile in both groups. References: Hoyer-Kuhn H, Netzer C, Semler O. Osteogenesis imperfecta: pathophysiology and treatment. Wien Med Wochenschr 1946 2015;165:278–84. doi:10.1007/s10354–015–0361-x. Hald JD, Evangelou E, Langdahl BL, et al. Bisphosphonates for the Prevention of Fractures in Osteogenesis Imperfecta: Meta-Analysis of Placebo-Controlled Trials. J Bone Miner Res 2015;30:929–33. doi:10.1002/jbmr.2410. Disclosure of Interest: None declared